ANALISIS HIDROLOGI BENDUNG GEBONG KECAMATAN PRINGGARATE KABUPATEN LOMBOK TENGAH: Hydrological Analysis Of Gebong Weir Pringgarate District Central Lombok District - Putra, I Gede Maji Arya Duta Edy; Yamin, Muhamad; Aminullah, Aminullah (Yayasan Al-Amin Qalbu, 2024)
Every weir construction requires appropriate hydrological analysis so that the weir planning can be technically and economically appropriate. Apart from that, in the weir planning process it is necessary to optimize its storage, so that the weir function can run optimally. The aim of this research is to determine the availability of irrigation water needs in the Gebong Weir irrigation area. After calculating and analyzing rainfall data, researchers can draw conclusions regarding the availability and need for water for irrigation at Gebong Dam, that the availability of irrigation water for farmers is still sufficient, the first planting season is February, the available debit is 78,065,054 lt/sec/ha, the season the second planting season in June, the available debit was 3,261,647 lt/sec/ha and the third planting season in October the debit was 7,8343,683 lt/sec/ha, while the water requirement for Gebong irrigation in February was 271.77 lt/sec/ha, The water requirement for the second planting season in June is 272.31 lit/sec/ha and for the third planting season in October it is 272.74 lit/sec/ha